2022
DOI: 10.1080/13510002.2022.2062947
|View full text |Cite
|
Sign up to set email alerts
|

D-limonene (5 (one-methyl-four-[1-methylethenyl]) cyclohexane) diminishes CCl4-induced cardiac toxicity by alleviating oxidative stress, inflammatory and cardiac markers

Abstract: Background: The cardiovascular crisis is advancing rapidly throughout the world. A large number of studies have shown that plant polyphenols affect major mechanisms involved in cardiovascular events through their action on the antioxidant system, signaling, and transcription pathways. D-limonene, a monocyclic monoterpene obtained from citrus fruits, is reported to possess many pharmacological activities. Methods: The experiment was designed to determine the protective effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
0
11
0
1
Order By: Relevance
“…They inhibited lipooxygenase and decreased inflammatory markers like TNF-α and IL-6. 68 Additionally, new cyclohexane fused spiroselenuranes showed potent antioxidant activity. 69 It has been reported that some azaspiro compounds had antioxidant and antielastase activity, 70 as it was found that human neutrophil elastase modulates cytokine and growth factor expression.…”
Section: Resultsmentioning
confidence: 99%
“…They inhibited lipooxygenase and decreased inflammatory markers like TNF-α and IL-6. 68 Additionally, new cyclohexane fused spiroselenuranes showed potent antioxidant activity. 69 It has been reported that some azaspiro compounds had antioxidant and antielastase activity, 70 as it was found that human neutrophil elastase modulates cytokine and growth factor expression.…”
Section: Resultsmentioning
confidence: 99%
“…Limonene is a monoterpene with a citrus odor at room temperature, commonly found in plants of the Rutaceae family. It is abundant in citrus plants such as lemon, grapefruit, and orange and in grapes (Amini et al 2020;AlSaffar et al 2022). Monoterpenes are known to have anticancer properties (Sobral et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…d -Limonene ( 8 , Figure 4 ) is a chiral, cyclic monoterpene that has been shown to have both anticancer and antioxidant properties. A study conducted in vivo animal models showed this compound’s ameliorative effect on chloroform induced cardiotoxicity by lowering oxidative stress, inflammatory and cardiac markers [ 57 ]. The study monitored the change in cardiac injury markers whose expression was increased by CCl 4 ; following two weekly doses of 200 mg/kg of d -limonene approximately 50% reduction in serum levels of cardiac inflammatory markers IL-6, Hs-CRP, and TNFα was noted [ 57 ].…”
Section: Biological Activities Of Monoterpenesmentioning
confidence: 99%